Perbandingan Pengetahuan Ibu tentang Penanganan Pertolongan Pertama Luka Bakar pada Anak Menggunakan Media Booklet Di Klinik â€œBnâ€ Kabupaten Bandung Barat - Khumairani Tantri; Dyah Triwidiyantari; Sri Hennyati (Jurnal Sehat Masada, 2024)
Burns are an event that is quite difficult to avoid, especially among children, the inability of children to face challenges and determine a dangerous hazard. In addition, burns are injuries that often occur in life or daily activities, be it minor or severe burns. 1 Parents have a role to provide assistance to children. In everyday life the role of parents is important for the growth of children. Mother plays a special role in this. There are still many mothers who do not know how to provide first aid for burns such as giving toothpaste, butter, soy sauce, oil. physical limitations. This research is a quantitative study with the type of Pre-Experimental research. The research design used was the pre and post test one group design. Judging from the approach, this study uses a cross sectional approach. The sampling technique in this study was accidental sampling. before being given health education regarding the management of burns in children with booklet media, the results obtained were a minimum value of 17 and a maximum of 22, with a mean of 19.95 and a standard deviation of 1.753. after being given health education regarding the management of burns in children using booklet media, the results obtained were a minimum score of 17 and a maximum of 22, with a mean of 21.03 and a standard deviation of 1.405. After the Wicoxon T-Test was carried out, the results showed a Ï value of 0.000 with a significant level of 0.05. Based on these results, a value of 0.000 0.05 was obtained, this means that there was a significant effect on the difference in the treatment given to each variable. it is hoped that health workers, especially midwives, will increase the provision of information and counseling about the importance of handling first aid for burns in children to parents, both when mothers come to the clinic and when midwives make field visits such as posyandu, so that later parents can have an Good knowledge of first aid for burns.